Zina Menurut Ali Ash-Shabuni dalam Tafsir Shafwatu Tafasir - Ridho Riyadi (Universitas Darussalam Gontor, 2021)
Adultery is a very bad deed and a big sin for the Adulterer in Islam. However, In this modern era, many muslims still do it. Nevertheles, Muslims know about the prohibition of adultery. This paper is aimed to explore further the interpretation of adultery according to Ash-Shabuni in the tafsir book of Shafwatu Tafasir. This study used a library research method. The data collection method is based on literature from scientific books related to the problem of adultery. The results of the research according to Ash-Shabuni revealed that Adultery for unmarried adulterers (ghairu muhsan) were beaten a hundred times and exiled for a year while adultery for married offenders (muhsan) was stoned to death.